Analysis of physical, economic and social water efficiency in asparagus (Asparagus officinalis L.) and grape (Vitis vinifera) fruit from DR-037 of Altar-Pitiquito-Caborca, Sonora, Mexico 2014 - Ríos Flores , José Luis; Rios Arredondo, Becky Elizabeth; Cantú Brito , Jesús Enrique; Rios Arredondo, Hebrián Efraín; Erives, Sigifredo Armendáriz; Chávez Rivero, José Antonio; Navarrete Molina, Cayetano; Castro Franco, Rafael (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
This work estimated the efficiency of water in asparagus and vine crops in Irrigation District 037 through the use of indicators that allowed determining the physical, economic and social efficiency of water in the cultivation of asparagus versus table grape. Indicators of physical, economic and social efficiency of water were 2075 kg and 625 L-1 US$540,924 and $945,190 useful hm-3 and 48.6 and 10.7empleos hm-3 respectively for asparagus and vine. In conclusion, asparagus compared with table grapes is inefficient water use in physical and economic but not social terms, water use in asparagus generates 4.54 times more jobs per unit of water used. Of the 8,281 jobs, US$ 163.63 million of utility and 245.63 hm3 of water used by both crops, asparagus contributed with 91%, 56.3% and 69.2% respectively. In Caborca water is a scarce resource, however, even though the proportion utility m-3 / cost m-3 was 29.7, it places the regional water within what the economy called the tragedy of the common goods. Which has caused a serious problem of overexploitation of the aquifer, as the producer makes an inefficient use of water.